2015
DOI: 10.2174/1567205012666150710115506
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance as Common Molecular Denominator Linking Obesity to Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is an aging-related multi-factorial disorder to which metabolic factors contribute at what has canonically been considered a centrally mediated process. Although the exact underlying mechanisms are still unknown, obesity is recognized as a risk factor for AD and the condition of insulin resistance seems to be the link between the two pathologies. Using mice with high fat diet (HFD) obesity we dissected the molecular mechanisms shared by the two disorders. Brains of HFD fed mice showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 66 publications
12
101
0
2
Order By: Relevance
“…Finally, our in vivo data also supports increased levels and increased nuclear localization of Foxo3 in mouse brains upon Cdk5 activation, further underscoring the significance of this pathway in Alzheimer's disease pathogenesis. A recent study indeed showed increased levels of Foxo3 in the nuclei of neurons in mice with high fat diets where proapototic genes were activated (Nuzzo et al, 2015). Most importantly, these mice exhibited several Alzheimer's disease phenotypes including increased levels of APP, Aβ(1-40) and Aβ(1-42) along with BACE and tau proteins, which further exemplifies the significance of Foxo3 signaling in Alzheimer's disease pathogenesis.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, our in vivo data also supports increased levels and increased nuclear localization of Foxo3 in mouse brains upon Cdk5 activation, further underscoring the significance of this pathway in Alzheimer's disease pathogenesis. A recent study indeed showed increased levels of Foxo3 in the nuclei of neurons in mice with high fat diets where proapototic genes were activated (Nuzzo et al, 2015). Most importantly, these mice exhibited several Alzheimer's disease phenotypes including increased levels of APP, Aβ(1-40) and Aβ(1-42) along with BACE and tau proteins, which further exemplifies the significance of Foxo3 signaling in Alzheimer's disease pathogenesis.…”
Section: Discussionmentioning
confidence: 80%
“…Other risk factors can be coronary artery disease, high blood pressure (hypertension), stroke, serum cholesterol contents (Proitsi et al, 2014), etc. Recent studies suggest that metabolic syndromes, such as diabetes and obesity with insulin resistance, also play an important role in causing sporadic AD (de la Monte and Tong, 2009, 2014; Nuzzo et al, 2015). Diets containing high fat with or without high fructose/sucrose and sedentary life style may represent another risk factor that contributes to the cognitive decline in animal models (Agrawal et al, 2015; Chang et al, 2014; Liu et al, 2014b; McNeilly et al, 2012; Morrison et al, 2010).…”
Section: Mitochondrial Dysfunctions In Selected Neurodegenerative mentioning
confidence: 99%
“…Recently obesity was shown as another risk factor for AD in mice fed a high fat diet (HFD). In the brains of HFD-fed mice, the levels of APP and Aβ40/Aβ42 were significantly elevated in both hippocampal and cortical regions (Nuzzo et al, 2015). In addition, the decreased number of insulin receptors and the inhibition of Akt-Foxo3 signaling were observed.…”
Section: Mitochondrial Dysfunctions In Selected Neurodegenerative mentioning
confidence: 99%
“…In mice fed a high-fat diet (HFD), endogenous GLP2 acts as a protective factor against the dysregulation of glucose metabolism that occurs in HFD-fed mice because GLP2 (3-33) chronic treatment exacerbates glucose metabolism disorders . It is well known that in C57BL/6J mouse model, a chronic exposure to HFD induces obesity and a progressive deterioration of metabolic control, characterized by hyperglycaemia, hyperinsulinaemia and peripheral and central insulin resistance (Surwit et al 1988, Ahrén et al 1997, Lee et al 1995, Nuzzo et al 2015. Mice after 10 weeks on HFD have greater mass gain compared with standard diet-fed mice, show hyperglycaemia, an impaired glycaemic response following intraperitoneal glucose load, high plasma insulin level after glucose load, increased pancreas weight and β cell expansion, but not insulin resistance.…”
Section: Glp2 and Glycaemic Controlmentioning
confidence: 99%